Sikkim Draft Annual Plan 1995-96 (Volume-I) - Planning Commission (Planning Commission, 1994)
As regards irrigation, proposals have been designed to optimise utilisation of potentials created by restoring and making functional all defunct and damaged systems. Due care has also been taken to conserve the catchment areas of all water sources. Development of feeder channels to optimise the capacity utilisation has also been given specific attention. In the field of energy, there has been significant increase in the generation capacity and simultaneously remarkable progress has been made as regards improvement and extension of the Transmission and Distribution network. Unfortunately, due to the ecologically fragile terrain combined with the inclement weather conditions, the State suffered severe devastation resulting in destruction of major hydel systems.
Sikkim Draft Annual Plan 1995-96 (Volume-I)
Government of Sikkim